The Lawrence Jordan album - Jordan, Lawrence (Chicago : Facets Video, 2008)
Disc 1. Duo concertantes (9 min., 1961-1964) ; Gymnopédies (5 min., 1966) ; Our lady of the sphere (10 min., 1969) ; Orb (5 min., 1973) ; Once upon a time (12 min., 1974) ; Moonlight sonata (5 min., 1979) ; Carabosse (5 min., 1980) ; Masquerade (5 min., 1981) ; The Rime of the ancient mariner (42 min., 1977) ; Enid's idyll (17 min., 2004) -- ##Disc 2. The H.D. trilogy film (115 mid., 1990-1993) -- ##Disc 3. Sophie's place (86 min.) ; The Visible compendium (17 min., 1990) ; Blue skies beyond the looking glass (17 min., 2006) -- ##Disc 4. The sacred art of Tibet (28 min., 1970-1972) ; Cornell, 1965 (9 min., 1994-1979) ; Visions of a city (8 min., 1957-1979) ; Adagio (8 min., 1981) ; In a summer garden (15 min., 1982) ; Winter light (9 min., 1983) ; Odyssey: Waterlight (8 min., 1957), Tapestry (12 min., 1988), Postcard from San Miguel (10 min., 1996) -- ##Booklet: Landscapes of the mind : the films of Larry Jordan.
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Jordan, Lawrence